Strategi Menemukan Peluang Pasar Jasa Pendidikan Tinggi Dan Memenangkannya - M Johan Widikusyanto; Solehatin Ika Putri (FEB Universitas Sultan Ageng Tirtayasa, 2020)
Banten is a province that is rich in natural resource potential but lacks sufficient quality human resources. This condition causes Banten to become the province with the second highest unemployment rate in Indonesia.Higher Education has a role as well as a great responsibility to revise and improve the quality of human resources, as well as being able to survive and even win competition between universities in Banten. The segmenting, targeting and positioning strategy will help universities find market opportunities and make them the basis for developing marketing programs and the means to survive and win competition.Studies of segmenting, targeting and positioning strategies have been carried out in various industries, but only a few of these studies have been carried out in the higher education service industry.Increasing competition in the higher education service industry in Banten encourages the need for studies of this strategy, to help them survive and win competition, both against competitors from within and outside Banten.The purpose of this research is to formulate a segmenting, targeting and positioning strategy that can be used by universities in Banten as a basis for designing their marketing programs that effectively defend and win their markets.The survey research design was used to obtain data to be analyzed using the K mean Cluster, Cross Tabulation Method and Correspondent Analysis. The questionnaire was distributed to 500 third-grade high school students and their equivalents in Banten. Questionnaires that can be further processed are 493.This research produces four higher education service market segments that can be selected to be the target market. The four segments are, segment one is physical evidence oriented, segment two is oriented towards scholarship and academic services, segment three is cost oriented and segment four is process oriented education, graduates and prestige. Higher education institutions can choose one or more segments that they can serve better than competitors.Perception maps in this study show variations in the positions of eleven Higher Education Institutions in the minds of prospective students. Some universities have good positioning, while others have unclear and bad positioning. Higher Education Institutions can maintain their positioning or reposition if the existing positioning is not as intended. New players who will enter can use the perception map produced by this research to determine their positioning and the competitors they will face.